Bioconcentration, biotransformation and elimination of pyrene in the arctic crustacean Gammarus setosus (Amphipoda) at two temperatures. (September 2015) - Carrasco-Navarro, V.; Jæger, I.; Honkanen, J.O.; Kukkonen, J.V.K.; Carroll, JoLynn; Camus, Lionel
Abstract: The influence of temperature on the bioaccumulation, toxicokinetics, biotransformation and depuration of pyrene was studied in the arctic marine amphipod Gammarus setosus . A two-compartment model was used to fit experimental values of total body burden, total metabolites and parent pyrene concentrations and to calculate toxicokinetic variables derived for two experimental treatments (2 and 8 °C). No statistically significant differences were observed with temperature for these toxicokinetic variables or bioconcentration factors. Contrarily, the Q10 values suggested that the toxicokinetic variables ke and km were temperature-dependent. This may be explained by the high standard deviation of the Q10 values. Q10 is the variation in the rate of a metabolic reaction with a 10 °C increase in temperature. Depuration rate constants were calculated from linear best fit equations applied to measured pyrene concentrations over time during the depuration phase of the experiment. During depuration, the parent pyrene was eliminated in two stages with faster elimination observed at 8 °C compared to 2 °C. This finding was also indicated by the Q10 . No changes in total body burdens of metabolite concentrations were observed during the monitoring of depuration over a period of 96 h. The biotransformation pathway of pyrene in G. setosus was also investigated in this study with two main phase II biotransformation products discovered by liquid chromatography. These products are conditionally identified as the sulphate and glucose conjugates of 1-hydroxy-pyrene. Overall, the study contributes new knowledge to the understanding of the fate of PAHs in arctic biota. In particular, the study provides valuable insight into the bioaccumulation and biotransformation of an important PAH and its metabolites in a species that serves as both a predator and prey in the arctic ecosystem. Highlights: Toxicokinetics and biotransformation of pyrene was studied in amphipods at 2 & 8 °C. A two-compartment model was used to calculate toxicokinetic values. Pyrene was biotransformed and eliminated faster at 8 °C. Gammarus setosus biotransformed pyrene to at least two phase II metabolites. These metabolites were not excreted efficiently after 4d in clean water.